Graphene oxide as a new generation adsorbent for the removal of antibiotics from waters - ÇALIŞKAN SALİHİ, ELİF (TAYLOR & FRANCIS INC, 2021)
The presence of antibiotic molecules in the natural water sources is currently a huge problem due to the development of bacterial resistance. Graphene oxide (GO) has a large potential as a candidate for the applications of water treatment. In this paper, graphene oxide was tested as a new generation adsorbent for the removal of two antibiotics: trimethoprim (TMP) and isoniazid (INH). Both adsorption processes reached the equilibrium in less than 1 h. Maximum adsorption capacities were found to be 204.08 mg g(-1) for TMP and 13.89 mg g(-1) for INH. TMP adsorption on GO was favored in alkaline medium while the performance of GO for INH adsorption was better in acidic conditions.
Keywords: Antibiotics removal; graphene oxide; waste water treatment; trimethoprim; isoniazid; WASTE-WATER; AQUEOUS-SOLUTIONS; ACTIVATED CARBON; RESISTANCE GENES; ADSORPTION; PHARMACEUTICALS; SULFAMETHOXAZOLE; CONTAMINANTS; NANOMATERIALS; TRIMETHOPRIM